The market that never was: Turf wars and failed alliances in mobile payments - Ozcan, Pinar; Santos, Filipe M. (Strategic Management Journal, 2015)
In this inductive multiple‐case study set in the nascent market for mobile payments, we investigate how global firms from different industries attempt to define the architecture for a new market. We find that powerful players from different industries have difficulty in reaching agreement on the new market's architecture due to their history of dominance in their respective industries. This disagreement in turn leads to a weak compromise on market architecture and creates a vicious cycle of resource allocation deferment. We show that the nascent market is thus less likely to emerge despite country‐level attempts at resolving these issues. Our findings contribute to resource dependence theory and to theories of market emergence, and lead to a deeper understanding of when and how markets fail to emerge . Copyright © 2014 John Wiley & Sons, Ltd.